Continuous Spectrum LEDs Promote Seedling Quality Traits and Performance of Quercus ithaburensis var. macrolepis - Smirnakou, Sonia; Ouzounis, Theoharis; Radoglou, Kalliopi M. (Frontiers in Plant Science, 2017)
Regulation of the growth, development and quality of plants by the control of light quality has attracted extensive attention worldwide. The aim of this study was to present the effects of continuous LED spectrum for indoor plant pre-cultivation and to investigate the morphological and physiological responses of a common broadleaved tree species in Mediterranean environment, Quercus ithaburensis var. macrolepis at seedling developmental stage. Thus, the seedlings were pre-cultivated for 28 days, under five different LED light qualities: 1) Fluorescent (FL) as control light 2) L20AP67 (high in green and moderate in far-red), 3) AP673L (high in green and red), 4) G2 (highest in red and far-red), AP67 (high in blue, red and far-red) and 5) NS1 (highest in blue and green and lowest in far-red) LEDs. Further examination was held at the nursery for one year, on several seedling quality traits. Indeed, AP67 and AP673L triggered higher leaf formation, while L20AP67 positively affected seedling shoot development. NS1 and AP67 LED pre-cultivated seedlings showed significantly higher root fibrosity than those of FL light. Furthermore, NS1 and AP673L LEDs induced four-fold increase on seedling root dry weight than FL light. Hence, evaluating the seedling nursery performance attributes, most of those photomorphogenetic responses previously obtained were still detectable. Even more so, LED pre-cultivated seedlings showed higher survival and faster growth indicating better adaptation even under natural light conditions, a fact further reinforced by the significantly higher Dickson’s Quality Index acquired. In conclusion, the goal of each nursery management program is the production of high quality seedlings with those desirable traits which in turn satisfy the specific needs for a particular reforestation site. Thus, the enhanced oak seedling quality traits formed under continuous LEDs spectrum especially of NS1 and AP673L pre-cultivation may potentially fulfill this goal.